Development of a Shipping Higher Education Curriculum that is Responsive to the Challenges of Industry 4.0 - Marsudi, Sugeng (Department of Ocean Engineering, Faculty of Engineering, Hasanuddin University, 2023)
The rapid development of technology and the emergence of Industry 4.0 have brought new challenges to the field of shipping studies. To prepare students for this challenge, it is necessary to develop a curriculum that is responsive to the changing needs of the industry. This study aims to explore the development of a higher education curriculum for maritime studies at the Vocational Shipping Studies Faculty at Hang Tuah University that is responsive to the challenges of Industry 4.0. This study uses a qualitative research design, using a review of relevant literature and documents. The objective of research is the higher education curriculum for maritime studies at the Faculty of Vocational Sailing Studies at Hang Tuah University. Data obtained through review of relevant documents from experts. The findings show that responsive curriculum development requires a thorough understanding of industry needs and expectations, as well as a commitment to continuously improve and adapt. Based on these findings, this research proposes a framework for the development of a responsive higher education curriculum for maritime studies that incorporates elements such as industry collaboration, competency-based learning, and integration of technology and digital skills. This research has important implications for institutions seeking to develop curricula that are responsive to changing industry needs, and can contribute to the development of a skilled and competent workforce in the field of shipping studies